Is the standard artificial urinary Sphincter AMS 800 still a treatment option for the irradiated male patient presenting with a devastated bladder outlet? - Queißert, Fabian; Hüsch, Tanja; Kretschmer, Alexander; Kirschner-Hermanns, Ruth; Pottek, Tobias; Olianas, Roberto; Friedl, Alexander; Homberg, Roland; Pfitzenmaier, Jesco; Naumann, Carsten M.; Nyarangi-Dix, Joanne; Hofmann, Torben; et al. (Journal of Clinical Medicine, 2023)
Background: Circular urethral compression with an artificial sphincter allows control of voiding, even in patients with severe stress urinary incontinence, but it heightens the risk of urethral atrophy and erosion. This study of one of the largest populations of patients treated with radiotherapy investigates the additive effect of the post-radiogenic stricture of the membranous urethra/bladder neck on AMS 800 artificial urinary sphincter outcomes. Methods: In a retrospective multicenter cohort study, we analyzed patients fitted with an AMS 800, comparing those who had received radiotherapy with patients presenting a devastated bladder outlet (stricture of the membranous urethra/bladder neck). We determined the correlation between these groups of patients using both univariate and stepwise adjusted multivariate regression. The revision-free interval was estimated by a Kaplan-Meier plot and compared by applying the log-rank test. A p value below 0.05 was considered statistically significant. Results: Of the 123 irradiated patients we identified, 62 (50.4%) had undergone at least one prior desobstruction for bladder-neck/urethra stenosis. After a mean follow-up of 21 months, the latter tended to achieve social continence less frequently (25.7% vs. 35%; p = 0.08). Revision was required significantly more often for this group (43.1% vs. 26.3%; p = 0.05) due to urethral erosion in 18 of 25 cases. A stenosis recurred in five cases; desobstruction was performed in two cases, leading to erosion in both. Multivariate analysis revealed a significantly higher risk of revision when recurrent stenosis necessitated at least two prior desobstructions (HR 2.8; p = 0.003). Conclusions: A devastated bladder outlet is associated with a lower proportion of men with social continence and a significantly higher need for revision compared with irradiated patients without a history of urethral stenosis. Alternative surgical procedures should be discussed beforehand, especially in cases of recurrent urethral stenosis.
Gesehen am 03.07.2024